A self‐consistent scattering model for cirrus. II: The high and low frequencies. (7th August 2013) - Baran, Anthony J.; Cotton, Richard; Furtado, Kalli; Havemann, Stephan; Labonnote, Laurent‐C.; Marenco, Franco; Smith, Andrew; Thelen, Jean‐Claude
Abstract The predictive quality of an ensemble model of cirrus ice crystals to model passive and active measurements of ice cloud, from the ultraviolet (UV) to the microwave, is tested. The ensemble model predicts m ∝ D2, where D is the maximum dimension of the ice crystal, and m is its mass. This predicted m‐D relationship is applied to a moment estimation parametrization of the particle size distribution (PSD), to estimate the PSD shape, given ice water content (IWC) and in‐cloud temperature. The same microphysics is applied across the electromagnetic spectrum to model UV, infrared, microwave and radar observations. The short‐wave measurements consist of airborne UV backscatter lidar (light detection and ranging) estimates of the volume extinction coefficient, total solar optical depth, and space‐based multi‐directional spherical albedo retrievals, at 0.865 µm, between the scattering angles 85° and 125°. The airborne long‐wave measurements consist of high‐resolution interferometer upwelling brightness temperatures, obtained between the wavelengths of about 3.45 µm and 4.1 µm, and 8.0 µm to 12.0 µm. The low‐frequency measurements consist of ground‐based Chilbolton 35 GHz radar reflectivity measurements and space‐based upwelling 190 GHz brightness temperature measurements. The predictive quality of the ensemble model is demonstrated to be generally within the experimental uncertainty of the lidar backscatter estimates of the volume extinction coefficient and total solar optical depth. The ensemble model prediction of the high‐resolution brightness temperature measurements is generally within ±2 K and ±1 K at solar and infrared wavelengths, respectively. The 35 GHz radar reflectivity and 190 GHz brightness temperatures are generally simulated to within ±2 dBZe, and ±2 K, respectively. The directional spherical albedo observations suggest that the scattering phase function of the most randomized ensemble model gives the best fit to the measurements (generally within ±3%). This article demonstrates that the ensemble model, assuming the same microphysics, is physically consistent across the electromagnetic spectrum.